Enhancing line loadability in urban rail systems: evaluating the impact of distributed generation on voltage stability, power losses and generation costs - A Wahab, Amirul Sufie; Ali, Adlan; Emran, Muhammad Helmy; Ramli, Mimi Faisyalini; Mohd Yassim, Halyani; Mohamed Ghazali, Auni Najihah (Learning Gate, 2024)
Alternative source of electrical energy for urban railway electrification system is Direct Current (DC). Traction Power Substations (TPS) were essentially connected to the electrical grid network managed by the electrical utility company for operating and powering purposes. Power unbalance frequently occurs in the high voltage railway network due to the load of the traction system. The aim of this project is to find the impact of distribution generation (DG) for line loadability in urban rail systems. The output that needs to be considered are the voltage profile, power losses and generation cost. The simulation was considered to prove the positive impact of distributed generation for line loadability in urban rail system. Electrical energy was crucial for Direct Current (DC) railway electrification systems, as it provided the traction power necessary for train operations via Traction Power Substations (TPS) that connected to the electrical grid network. However, power imbalances frequently arose due to the varying loads imposed by traction systems, resulting in inefficiencies, suboptimal voltage profiles, increased power losses and higher operational costs. With the expansion of urban rail networks and the growing need for efficient power management, it became vital to explore solutions that could enhance loadability and system performance. This project examined the impact of integrating Distributed Generation (DG) on the line loadability of urban rail systems, concentrating on improvements in voltage profiles, reductions in power losses and the evaluation of generation costs. The methodology involved developing a detailed simulation model of the urban rail system, incorporating DG scenarios, analyzing their effects on voltage stability, power losses and costs. The simulation results were anticipated to demonstrate that DG could improve voltage stability, reduce power losses, lower generation costs and increase line loadability. The implications of these findings encompassed enhanced operational efficiency, potential economic benefits despite high initial investments, increased sustainability through renewable energy and valuable guidance for future infrastructure development and investment decisions.